Legal and Ethnoracial Consciousness: Perceptions of Immigrant Media Narratives Among the Latino Undocumented 1.5 Generation. (November 2022) - Vaquera, Elizabeth; Castañeda, Heide; Aranda, Elizabeth
Prior work has focused on the role of media in shaping public perceptions of immigrants and in the construction of social illegality. In this article, we examine how the undocumented 1.5 immigrant generation perceive, consume, and navigate media messaging about immigration—and particularly Latino immigrants—to understand the role of media in shaping their lived experiences. We analyze 50 in-depth and nine follow-up interviews with undocumented young adults in Florida collected between 2017 and 2021. Two major themes emerged: (1) how media information and misinformation invoke both legal and ethnoracial consciousness; and (2) how undocumented young immigrants deploy agentic strategies to resist negative and dehumanizing portrayals by rejecting media altogether, leveraging media to resist abuses, and embracing counter-narratives. Based on these findings, we discuss the usefulness of a double consciousness framework and argue for the use of "ethnoracial consciousness" in synergy with legal consciousness to more accurately describe experiences for this population.